A Design Science Roadmap for Auditable Ocular Disease Classification: Evidence Mapping of AI Governance Gaps - Rizal Rachman (Asosiasi Pengelola Jurnal Informatika dan Komputer Indonesia, 2026)
The integration of Artificial Intelligence (AI) into ocular diagnostics has led to substantial improvements in predictive accuracy. However, a persistent gap remains between technical performance and clinical accountability. The present study addresses the